«Umgekehrt wird man leicht selbst zum Verfolgten»: the structure of the double-bind in W.G. Sebald - Hutchinson, Ben (Revista de Filología Alemana, 2006)
W.G. Sebald’s engagement in his first book Schwindel. Gefühle with Kafka suggests a hauntingly ambivalent relationship with his literary predecessors. His narrator is both «passive» and «active» in Nietzsche’s terms, hunted by history as much as the hunter of his story. In this paper I attempt to address two main areas: in the first half I examine the ambivalence of this intertextuality, whilst in the second half I consider examples of how this ambivalence is enacted in the structures of his syntax, drawing in particular on Sebald’s annotations in his own personal ‘Handbibliothek’. My central contention is that both his engagement with his chosen predecessors, as well as his circular syntax, can be characterized as (in his own words) «eine klassiche Situation des double-bind».